Measurements of size and composition of particles in polar stratospheric clouds from infrared solar absorption spectra - Kinne, S.; Toon, O. B.; Toon, G. C.; Farmer, C. B.; Browell, E. V.; Mccormick, M. P. (1989)
Results are presented on polar stratospheric cloud (PSC) observations, based on IR measurements of solar extinction, made by the airborne JPL Mark IV interferometer during the Airborne Antarctic Ozone Expedition in 1987, together with the instrumentation and the theoretical aspects of data analysis. Thirty-three PSC cases were analyzed and categorized into two types, I and II, which were found to occur at different altitudes during September. Type I clouds, seen at altitudes above 15 km, contained particles with radii of about 0.5 micarons and nitric acid concentrations greater than 40 percent, while type II clouds, found usually below 15 km, contained particles with radii of 6 microns and larger, composed of water ice. In addition, particles of larger than the 15-micron-size detection limit were encounterd.